Medicinal plants: main alternative for health care, in the rural town of Babahoyo, Ecuador - Gallegos Zurita, Maritza (2016)
Introduction. The therapeutic use of medicinal plants, as a substitute for pharmaceutical drugs, has been applied since ancient times to cure or relieve disease; however, there is still not enough evidence to strengthen herbal medicine within health systems. Objectives. To identify the usual practices of health care, developed by the rural population of Babahoyo, Ecuador. Design. Ethnographic qualitative study; quantitative observational and transversal study. Setting. Babahoyo, Ecuador rural population. Participants. Family heads 17 to 72 years old, 58% female and 42% men. Methods. In depth interviews were conducted using orienting questions, applied to focus groups, to learn about their ideas, beliefs, meanings, regarding health care practices. Main outcome measures. Health care practices, diseases treated with medicinal plants. Results. Three health care practices and 44 diseases treated with medicinal plants were identified. The most common diseases were: digestive and parasitic diseases (22.5%), inflammations in general (18.9%); diseases of the skin (11.3%), and respiratory diseases (8.1%). In addition, 63 species of plants with different therapeutic applications were identified. 99.4% of the population declared the intake of plants does not produce negative effects. However, they limit their use during pregnancy, allergies, ‘inebriated status’ and advanced diseases limited their intake. Conclusions. The rural population uses medicinal plants as an alternative for health care (59.4%); only in the event of major complications they seek medical attention (38.7%); just 0.9% received care from ‘healers’.